Il ruolo dell’orientamento universitario in itinere per la prevenzione del drop-out e la promozione del successo formativo. Una rassegna di studi empirici recenti - Conny De Vincenzo (Journal of Educational, Cultural and Psychological Studies, 2021)
Guidance activities are considered as a valid support for the individual along his or her entire educational path, from the first years of school until the transition to the job market; in particular, the crucial function of this type of activity has been pointed out in the first phase of university studies. This paper presents a reasoned review of the literature on the main ongoing university guidance interventions, with particular attention to the prevention of drop-out and the promotion of academic success. Previous studies highlighted the role that ongoing guidance can play in the prosecution of studies and in reducing drop-out rates, as well as in favouring the integration of the subject in the academic context and raising awareness of his or her goals. Nonetheless, in the literature there is no univocal consensus regarding the fundamental characteristics of an effective guidance intervention. Starting from a critical analysis of some recent results, the main methodological issues of guidance research are illustrated, with particular reference to the strategies for evaluating the efficacy of interventions. In line with the main previous reviews, the need to conduct systematic studies guided by empirical evidence is emphasised, using rigorous research designs to identify the factors involved in the effectiveness of ongoing university guidance.